1988
DOI: 10.3109/00365528809090173
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Ascitic Fluid Cholesterol Levels in the Prediction of Malignancy

Abstract: In a prospective study abdominal paracentesis with ascitic fluid aspiration was performed in 54 consecutive patients with ascites of unknown cause. The ascitic fluid was examined cytologically and bacteriologically. The total cholesterol concentration was measured with an enzymatic colorimetric method. Malignant disease was diagnosed in 34 patients. Two of them had both malignant disease and liver cirrhosis and were excluded. Seventeen patients had liver cirrhosis, one had acute pancreatitis, and two had decom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…TCH may originate in cell membranes, perhaps as a result of disintegration of tumor cells and/or surrounding benign cells [8,13]. It can also enter the cavity from the interstitial space because of obstructed lymph vessels or be related to increased permeability of the carcinomatous serous membrane [16,33]. Raised cholesterol concentrations have also been reported in inflammatory conditions involving the peritoneum and associated with chronic cardiac congestion [16,34].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…TCH may originate in cell membranes, perhaps as a result of disintegration of tumor cells and/or surrounding benign cells [8,13]. It can also enter the cavity from the interstitial space because of obstructed lymph vessels or be related to increased permeability of the carcinomatous serous membrane [16,33]. Raised cholesterol concentrations have also been reported in inflammatory conditions involving the peritoneum and associated with chronic cardiac congestion [16,34].…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, complete separation between malignant ascites and nonmalignant ascites has not been always possible. To increase diagnostic efficiency, cytologic evaluation has been coupled with the analysis in both serum and ascitic fluid for total protein [10,11], various enzymes [9], fibronectin [11,12], tumor antigens [13,14], and lipids [15][16][17], etc.…”
Section: Introductionmentioning
confidence: 99%
“…The most reliable way to exclude involvement of the peritoneum by a tumour is to perform a thorough postmortem examination, and results that are not corrected for inadequate follow up are diYcult to interpret. 13 In our study, we investigated the possible additional value of cholesterol and CEA assays to ascites cytology-in particular, when the cytological findings alone are inconclusive. In all cases, the results of cytological and chemical analyses were related to the stratified true diagnosis-that is, the presence or absence of peritoneal malignancy, as established at necropsy and/or histological examination.…”
mentioning
confidence: 99%
“…In an additional study, markedly elevated concentrations of total cholesterol were found in malignant and inflammatory ascitic fluid compared to ascites from patients with cirrhosis (2). Recently these findings have been confirmed and the clinical value of ascitic cholesterol to differentiate between cirrhotic and malignant ascites has been established (3)(4)(5)(6)(7). The pathogenesis of high ascitic cholesterol levels in patients with malignant disease is not fully understood.…”
mentioning
confidence: 85%
“…It has been demonstrated that ascites cholesterol concentrations are markedly elevated in peritoneal carcinomatosis compared to cirrhosis and ascites cholesterol has been established as a parameter useful for the differential diagnosis of ascites (3)(4)(5)(6)(7). In an attempt to explain the elevated cholesterol concentration in malignant ascites, we compared the ascites to serum relation of proteins and lipoproteins in patients with cirrhosis or peritoneal carcinomatosis.…”
Section: Isesssionmentioning
confidence: 99%